2017
DOI: 10.18632/oncotarget.21037
|View full text |Cite
|
Sign up to set email alerts
|

MiR-143 inhibits endometrial cancer cell proliferation and metastasis by targetingMAPK1

Abstract: Endometrial cancer (EC) is one of the most commonly diagnosed gynecologic malignancies in the world, with the morbidity rate of over 7%. The mechanism of the pathogenesis has not been specifically elucidated to date, which is imperative for EC treatment. The aim of our study was to investigate the target relationship between miR-143 and mitogen-activated protein kinase 1 (MAPK1) and explore the effect of miR-143 on the endometrial cancers (EC) cells through targeting MAPK1. We collected EC tissues and adjacent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 44 publications
3
22
0
1
Order By: Relevance
“…Hu et al shed light on the role of miR-585 in targeting MAPK1 and inhibiting gastric cancer cell proliferation and migration [29]. Furthermore, Chang et al applied a series of assays to witness that miR-143 might suppress the proliferation, migration and invasive ability of Endometrial cancer (EC) cells while promote the EC cells apoptosis by decreasing MAPK1 [30].…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al shed light on the role of miR-585 in targeting MAPK1 and inhibiting gastric cancer cell proliferation and migration [29]. Furthermore, Chang et al applied a series of assays to witness that miR-143 might suppress the proliferation, migration and invasive ability of Endometrial cancer (EC) cells while promote the EC cells apoptosis by decreasing MAPK1 [30].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the MAPK/ERK signaling pathway is a key signaling pathway of RAS networks, which play a role in metastasis. In endometrial cancer (EC), the downregulation of MAPK1 was observed with the ectopic expression of MIR143 and the suppression of invasion and migration was observed 63 …”
Section: The Role Of Mir143‐3p On Rat Sarcoma Signaling Network In Vmentioning
confidence: 99%
“…In summary, a lot of miRNAs, cellular and circulating, have been found dysregulated in endometrial cancer and a comprehensive list and the relative references are reported in Table 2 [ 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ].…”
Section: Ncrnas and Endometrial Cancermentioning
confidence: 99%